COMMUNITY EMPOWERMENT IN FUND ALLOCATION LONG TUNGU VILLAGE, PESO HILIR DISTRICT, BULUNGAN REGENCY - Vivilitan Vivilitan; Shahran Shahran; Rini Yayuk Priyati; Achmad Daengs GS (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
The research is motivated by the quality of village government officials in carrying out their duties and responsibilities, even though the quality of human resources is very important in the success of community empowerment programs and activities in Long Tungu Village. The purpose of this study is to analyze 1) the condition of community empowerment in the allocation of village funds in Long Tanggu Village, Peso Hilir District, Bulungan Regency; and 2) things that support and hinder community empowerment in the allocation of village funds in Long Tungu Village, Peso Hilir District, Bulungan Regency. The informants of this research are policy makers, policy implementers and users. The research method used is descriptive qualitative method. The technical analysis of the data used in this study starts from data collection followed by data reduction, data display and the last stage is drawing conclusions. The results of this study include: 1) the condition of community empowerment in the allocation of village funds in Long Tungu Village, Peso Hilir District, Bulungan Regency has been running well. 2) Supporting factors in the village fund allocation process include good cooperation between the village fund allocation management organization and the community, government support, local community support and technological developments. While the factors that hinder the process of managing the allocation of village funds from the district government to the village government, especially in Long Tungu, are: the quality of human resources, the ability of institutions in financial management that has not been maximized so that the disbursement of old funds. Keywords: village funds, community empowerment, allocation.